Histologic Examination of an Assemblage of Psittacosaurus (Dinosauria: Ceratopsia) Juveniles From the Yixian Formation (Liaoning, China). Issue 5 (2nd March 2016) - Bo, Zhao; Hedrick, Brandon P.; Chunling, Gao; Tumarkin‐Deratzian, Allison R.; Fengjiao, Zhang; Caizhi, Shen; Dodson, Peter
ABSTRACT: Psittacosaurus is one of the most abundant dinosaurs known, which allows for extensive study of its growth and form. Previous studies have evaluated growth trajectories of Psittacosaurus using bone histology. However, we present the first study of Psittacosaurus comparative juvenile histology and describe the histology of Psittacosaurus within its first year of life based on multiple sections taken from an exquisite monospecific assemblage of juveniles from the Yixian Formation in Liaoning, China. Specimens studied had femur lengths ranging from 30 to 36 mm. The five juveniles examined all have similar histologic patterns in the midshaft and epiphyseal regions showing that there is limited plasticity in bone development in juvenile Psittacosaurus and that all of the specimens in the assemblage were likely the same age. The microstructure patterns are compatible with the hypothesis that Psittacosaurus was precocial and that these juveniles were neonates. Based on comparisons with other juvenile ornithischians, juvenile Psittacosaurus had a growth rate similar to Orodromeus, slower than that of Maiasaura, Dysalotosaurus, or hadrosaurs consistent with small body size. Our results support previous studies that demonstrated that the orientation of vascular canals is likely not solely reflective of growth rate, but is also affected by underlying biomechanical, structural processes. The number of studies done on theropod and sauropodomorph histology dwarfs those of ornithischians. More studies of ornithischian histology are necessary in order to better establish phylogenetic trends in microstructure and to learn more about growth in this important clade. Anat Rec, 299:601–612, 2016. © 2016 Wiley Periodicals, Inc.